Meaning of Ornaments in Pakpak Traditional House: Semiotic Study - Tampubolon, Flansius; Sinulingga, Jekmen (Budapest International Research and Critics University, 2020)
This study aims to explore the meaning of the Pakpak traditional house ornament. This study reveals the meaning that symbolically represents cultural values in the Pakpak community. This study uses a semiotic approach with qualitative descriptive research methods. The ornaments in the Pakpak traditional house imitate the shapes associated with human limbs, in the form of animals, in the form of plants and resembling the cosmos or nature. Each form of ornament has a meaning which is the cultural values that the Pakpak community believes in.